2015
DOI: 10.11648/j.cmr.s.2015040201.13
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Induced Neurocognitive Impairment (Wernicke - Korsakoff): A Hidden Syndrome

Abstract: Wernicke's encephalopathy (WE) is an acute neuro-psychiatric syndrome due to inadequate supply of thiamine (vitamin B1) to the brain which leads to significant morbidity and mortality. Although alcohol use is the most common predisposing factor but Wernicke's encephalopathy can occur in any patient with nutritional deficiency conditions such as hyperemesis gravidarum, hemodialysis, malignancy, use of total parenteral nutrition without adequate thiamine, and abdominal surgery. In a developing country, there are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 77 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…Wernicke encephalopathy (WE) was described by Carl Wernicke in 1881, being characterized by the clinical triad of encephalopathy, ophthalmoparesis, and ataxia (3), secondary to the deficiency of thiamine. Recent studies have demonstrated a high prevalence (about 70%) of thiamine deficiency in critical patients with sepsis (4).…”
Section: Introductionmentioning
confidence: 99%
“…Wernicke encephalopathy (WE) was described by Carl Wernicke in 1881, being characterized by the clinical triad of encephalopathy, ophthalmoparesis, and ataxia (3), secondary to the deficiency of thiamine. Recent studies have demonstrated a high prevalence (about 70%) of thiamine deficiency in critical patients with sepsis (4).…”
Section: Introductionmentioning
confidence: 99%